The structure of wellbeing: study among algerian workers using structural equation modeling (مجلة الواحات للبحوث والدراسات, 2021)
Wellbeing today is a magnet that brings the concerns of many researchers in the humanities and social sciences in general and psychology more precisely; especially the trend of positive psychology. Wellbeing is the cornerstone of most international and national programs and strategies that wish to achieve a prestigious position of the individual in the environment he lives in. In this context, our present study aimed to explore the structure of wellbeing in the Algerian work environment, starting from new and different theoretical conception of wellbeing new and different, but depends in large part on three of the models presented by a number of researchers, which are widely spread and employed in wellbeing studies. The main objective of this study was to test the model proposed by us using structural equation modeling on a sample of 1362 workers from the public and private sector in three states of Algeria, The result shows that the proposed model has good fit indicators, that is, it actually reflects the structure of wellbeing in the study population.Keywords: Wellbeing, Model, Structural Equation Modeling, Happiness, Algerian Worker.